Fix it in post solutions for postproduction problems - James, Jack 1977- (Amsterdam Boston Focal Press, 2009)
This book provides an array of concise solutions to the wide variety of problems that are faced by postproduction artists in the post process. With an application-agnostic approach, it gives proven, step-by-step methods to solving the most frequently encountered postproduction problems. Solutions are provided for common audio, video, digital, editorial, color, timing and compositing problems.--From publisher description.
E2-1686: Prof. Rhandley Cajote (recommending faculty)
Keywords: Motion pictures -- Editing -- Data processing; Video tapes -- Editing -- Data processing